Effects of Moringa oleifera leaves on CRP, MDA, and alevels in a mouse model of preeclampsia - Nutria Widya Purna Anggraini; Sri Sulistyowati; Soetrisno Soetrisno; Bambang Purwanto; Paramasari Dirgahayu (Open Veterinary Journal)
Background: Preeclampsia is a serious pregnancy complication characterized by high blood pressure and organ dysfunction, primarily affecting the placenta and kidneys. Reduced placental blood flow can have severe consequences for both the mother and fetus, highlighting the need for effective treatment options. Moringa oleifera leaves,which are known for their potent antioxidant and antiinflammatory properties, have been explored as a potential intervention to mitigate oxidative stress associated with preeclampsia.